Technical Barriers to Trade of Leather and Footwear: Impacts and Challenges Posed by International Standards, Regulations and Market Requirements in Brazil - Ruiz, Mauro Silva; Aguiar, Alexandre de Oliveira e; Cortez, Pedro Luiz; Teixeira, Cláudia Echevenguá; Graudenz, Gustavo Silveira (IntechOpen, 2012)
None